Drivers of Young Consumers’ Willingness to Reduce Food Waste and Buy Intelligent Packaging - Suwandi, Hendy; Bakrie, Nyiayu Rania Zalfaa; Vianney, Aurelia; Hendriana, Evelyn (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: As food waste harms the sustainable environment and the economy, some innovations have been made to reduce this issue, such as intelligent packaging. However, the factors leading to consumer behavior to reduce food waste and buy intelligent packaging, particularly in developing countries are still untapped.Methodology: This study aims to examine the relationship between green perceived value, intention to reduce food waste, and willingness to purchase intelligent packaging. Data from 230 Indonesian young consumers were analyzed using PLS-SEM.Finding: The results showed that different elements of green perceived value had significant effects on the intention to reduce food waste and willingness to purchase intelligent packaging. Unlike the predicted relationship, the intention to reduce food waste was not significant enough to lead consumers to purchase intelligent packaging.Conclusion: The presented study gives insights to businesspeople on which green perceived values are important for reducing food waste and encouraging consumers to buy intelligent packaging.